The Synthesis and Evaluation of anti-tubercular activity for some new 4-4-[(hydrazinylmethoxy) (hydroxy)methyl]phenyl-3-methyl-3,4dihydro quinoxalin -2(1H)-one novel Derivatives. - Potadar, Shripad; Kotnal, Ramling (Journal of Biomedical and Pharmaceutical Research, 2019)
A new series of 4-4-[(hydrazinylmethoxy)(hydroxy)methyl]phenyl-3-methyl-3,4dihydro quinoxalin -2(1H)-one were designed and synthesized in order to evaluate their anti-tb activity. The structure of the synthesized compounds was confirmed by elemental analysis and spectral data (IR, 1H NMR and Mass). The data obtained from biological screening revealed that; synthesized compounds showed the good to moderate anti-tb activities. Keywords: Quinoxaline, ortho-phenylenediamine and hydrazinehydrate.